Fundamentals of Powder Diffraction and Structural Characterization of Materials - Pecharsky, Vitalij K. (Springer, 2017)
This new edition provides an in-depth introduction to the theories and applications of the powder diffraction method for structure determination. The emphasis is placed on powder diffraction data collected using conventional x-ray sources, which remain primary tools for thousands of researchers and students in their daily experimental work. The book is divided into two parts: chapters one though fifteen give essential theoretical background, while chapters sixteen through twenty-five guide the reader through practical aspects of extracting structural information from powder data.